OZONE A new medical drug - Bocci, Velio; SpringerLink (Online service) (Dordrecht : Springer Netherlands : Imprint: Springer, 2011)
Oxygen-Ozone therapy is a complementary approach less known than homeopathy and acupuncture because it has come of age only three decades ago. This book clarifies that, in the often nebulous field of natural medicine, the biological bases of ozone therapy are totally in line with classical biochemistry, physiological and pharmacological knowledge. Ozone is an oxidizing molecule, a sort of super active oxygen, which, by reacting with blood components generates a number of chemical messengers responsible for activating crucial biological functions such as oxygen delivery, immune activation, release of hormones and induction of antioxidant enzymes, which is an exceptional property for correcting the chronic oxidative stress present in atherosclerosis, diabetes and cancer. Moreover, by inducing nitric oxide synthase, ozone therapy may mobilize endogenous stem cells, which will promote regeneration of ischemic tissues. The description of these phenomena offers the first comprehensive picture for understanding how ozone works and why. When properly used as a real drug within therapeutic range, ozone therapy does not only does not procure adverse effects but yields a feeling of wellness. Half the book describes the value of ozone treatment in several diseases, particularly cutanious infection and vascular diseases where ozone really behaves as a (3z(Bwonder drug(3y(B. The book has been written for clinical researchers, physicians and ozone therapists, but also for the layman or the patient interested in this therapy.s
Introduction -- Chapter 1 Physical-chemical properties of ozone. natural production of ozone. the toxicology of ozone -- Chapter 2 How ozone is generated and its concentrations measured? -- Chapter 3 Preparation of ozonated water and oil for the topical therapy. ozone as a drinking water disinfectant. ozone disinfection to prevent nosocomial infections.-Chapter 4 How does ozone act? how and why can we avoid ozone toxicity? -- Chapter 5 How is ozone administered? -- Chapter 6 The actual six therapeutic modalities -- Chapter 7 The potential toxicity of ozone. side effects and contraindications of ozone therapy -- Chapter 8 Is ozone really a (3z(Bwonder drug(3y(B? -- Chapter 9 The clinical application of ozone therapy -- Chapter 10 The dilemma between hyperbaric oxygen therapy (hot) and ozone therapy -- Chapter 11 The promising future of ozone therapy in medicine.s
Keywords: Medicine; Human physiology; Microbiology; Mass spectrometry; Dentistry; Cytology; Medicine & Public Health; Medicine/Public Health, general; Dentistry; Mass Spectrometry; Oxidative Stress; Human Physiology; Medical Microbiology